Metropolitan areas in a learning society: ICT-policy in the Netherlands as an example - Marina van Geenhuizen (European Regional Science Association (ERSA), 2002)
Metropolitan areas are often seen as suffering from negative externalities of a high density of activities and interaction. At the same time, high densities and a high variation of activities may contribute to a high level of innovation in urban activities. Various societal issues are addressed in policy-making for metropolitan areas today, like a continued economic growth based on a strong competitive position and on sustainability, enhancement of spatial quality in view of revitalisation of old urban areas and increasing of social cohesion, and improvement of accessibility of working and living places. The paper presents the outline and approach of a new study undertaken in the Netherlands to analyse the state and changes of the Randstad and to design trajectories for future development. First an analysis is given of what the Randstad is as a network of cities, mainly based on the recent literature. Three characteristics of the study are then highlighted, i.e. the approach which is a spatial systems approach, the role assigned to technology as a 'driver' of solutions for problems of urban capacity, and the emphasis on urban policy making as management of transition, including self-organisation. Policy issues raised in the Randstad are illustrated with the development of financial services in the two largest cities in the Randstad, i.e. Amsterdam and Rotterdam. Key words: metropolitan areas, urban problems, policy making, financial services
Keywords: 330